Tacticity, Isomeric Structural Units and Molecular Weight Determination of Hydroxyl Terminated Polybutadiene by High Field FT-qNMR Spectroscopy - Kumar Mahanta, Abhay (Asian Journal of Chemistry, 2012)
High field FT-qNMR (800 MHz) was used to determine the content of vinyl-1,2-unit in free radical as well as anionic hydroxyl terminated polybutadiene polymer. Two dimensional 1H/13C-HMQC was used to study the complex NMR spectrum. The 13C{1H} DEPT-135 experiment was carried out to differentiate between the methylene and methine carbon resonances. The tacticity was investigated by splitting the olefinic methylene carbons of 1,2-vinyl unit and was tested with Bernoullian and first-order Markov statistical model of chain propagation. The configurational sequence assigned to various methylene carbon resonances of the polymer are in good agreement with that calculated by the statistical models. The functionality, number-average degree of polymerization and molecular weight of the polymer were determined by FT-qNMR technique and the results were compared with those obtained by gel permeation chromatography.